Halitose bucal: importância da saburra lingual e periodontite na sua etiologia - Jardim Júnior, Elerson Gaetti [UNESP] (2012)
In general the human breath doesn't have smell or it is so only lightly perceptible to the surrounding ones, varying of pleasant the unpleasant, being taken in consideration the sensibility of the person. Halitosis or bad breath doesn't truly represent a disease, being present in a considerable portion of the population. Ethiologically exist several involved factors, could make an appointment breathing, gastric intestinal, organic and psychic disturbances and mainly oral factors, being the microbial colonization of the tongue the most common, beside the pathological situations involving periodontitis, as necrotizing ulcerative gengivitis. For representing a true obstacle biopsicossocial, the halitosis it influences directally in the family life, work, the patients' atmosphere social, being its diagnosis specific, demanding in certain occasions treatment multidisciplinar. In that sense, the present study if report to a literary revision of the theme, approaching the main aspects of the development of the halitosis, as well as its biological origin and its clinical implications.